Media Preference, Political Awareness & Participation: A Study Among University Students During 2017 U.P. Elections - Pandey, Pramod Kumar; Pathak, Charu Chandra (Journal of Advanced Research in Journalism & Mass Communication, 2017)
The research was undertaken to find out the media preference of the university students of western UP during the elections. The various media theories claim greater media dependence during times of greater importance. The researchers wanted to find out if the same applied to the elections as well. The researchers surveyed 150 university students using structured questionnaire. The findings suggest greater dependence on media during election times with different media preference for different type of information. The greater media consumption bears no significant association with the level of awareness regarding the politicians however the political engagement in other forms increases. How to cite this article: Pandey PK, Pathak CC. Media Preference, Political Awareness & Participation: A Study Among University Students During 2017 U.P. Elections. J Adv Res Jour Mass Comm 2017; 4(3&4): 61-67. DOI: https://doi.org/10.24321/2395.3810.201701